2007
DOI: 10.5751/ace-00201-020212
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Sampling Biases Associated with Roadside Bird Surveys

Abstract: Roadside surveys such as the Breeding Bird Survey (BBS) are widely used to assess the relative abundance of bird populations. The accuracy of roadside surveys depends on the extent to which surveys from roads represent the entire region under study. We quantified roadside land cover sampling bias in Tennessee, USA, by comparing land cover proportions near roads to proportions of the surrounding region. Roadside surveys gave a biased estimate of patterns across the region because some land cover types were over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Several previous studies have found variable bias in habitat representation and/or disturbance rates (Bart et al 1995, Keller and Scallan 1999, Lawler and O'Connor 2004, Betts et al 2007, Harris and Haskell 2007, Matsuouka et al 2011, Veech et al 2012. Our analyses suggested that bias was greatest in areas immediately along roadsides, which corresponds to work by Keller and Scallan (1999), who found a greater rate of increase in urban area along roadsides (0-200 m) than off-road areas (200-1600 m) in Maryland.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Several previous studies have found variable bias in habitat representation and/or disturbance rates (Bart et al 1995, Keller and Scallan 1999, Lawler and O'Connor 2004, Betts et al 2007, Harris and Haskell 2007, Matsuouka et al 2011, Veech et al 2012. Our analyses suggested that bias was greatest in areas immediately along roadsides, which corresponds to work by Keller and Scallan (1999), who found a greater rate of increase in urban area along roadsides (0-200 m) than off-road areas (200-1600 m) in Maryland.…”
Section: Discussionsupporting
confidence: 63%
“…First, our study implies that there is a risk of inaccurate status assessment for boreal forest birds. Simulations by Harris and Haskell (2007) suggest that habitat and disturbance biases can cause substantial misrepresentation of rates of population change, with one simulation suggesting underestimation of a population increase by 2.57% y -1 . Bias in that range could be sufficient to substantially change species status assessments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet avian abundance can be related to smaller scale habitats along roads or large-scale habitats surrounding the point count station at the landscape level. For example, accounting for habitat edges and narrow right-of-way roadside clearings may be helpful important when controlling for roadside bias (Harris and Haskell 2007). Furthermore, roadside bias has been found to be more prevalent along wider roads (Hutto et al 1995).…”
Section: Roadside Bias In Avian Survey Countsmentioning
confidence: 99%
“…For example, Western Meadowlarks are counted more often at survey points along roads due to their tendency to sing from fence posts (Rotenberry and Knick 1995). Similarly, there is a propensity of habitat edges along roadsides (Harris and Haskell 2007) and bird attracted to edges may be counted more frequently along roadside than off-road areas (Hutto et al 1995).…”
Section: Introductionmentioning
confidence: 99%